Answer:
The answer to your question is Center = (3 , -1), radius = 3
Explanation:
Equation
x² - 6x + y² + 2y = -1
-Process
1.- Leave a space between the like terms
x² - 6x + y² + 2y = -1
2.- Divide the middle term of each group by 2 and write the result to the power of 2 in both sides of the equation.
x² - 6x + (3)² + y² + 2y + (1)² = -1 + 3² + 1²
3.- Simplification
x² - 6x + 9 + y² + 2y + 1 = -1 + 9 + 1
4.- Factor
(x - 3)² + (y + 1)² = 9
5.- Find the center and the radius
Center = (3 , -1)
Radius = √9 = 3